2022
DOI: 10.1111/bjdp.12411
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for social withdrawal and academic adjustment in emerging adulthood

Abstract: While social withdrawal in childhood is typically associated with lower academic functioning, little is known about how motivations for social withdrawal may be connected to academic adjustment in emerging adulthood. The purpose of the present study was to examine associations between social withdrawal motivations (i.e., shyness, avoidance and unsociability) and indices of academic adjustment, including academic achievement (i.e., grade point average [GPA]) and academic motivation (i.e., intrinsic value, self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 98 publications
0
7
0
1
Order By: Relevance
“…We also investigated the links between solitary activities and adjustment outcomes such as feelings of loneliness, self-perceptions, emotional well-being, and personal happiness. Finally, based on past studies that suggest that solitary preferences and experiences may differ across adolescence (Hipson et al, 2021), and that girls and boys may have different motivations for being alone and have different thoughts and feelings while alone (McVarnock & Closson, 2022), we checked for differences in girls' and boys' responses, as well as between early and mid-late adolescence. Based on past research, we expected to find that older youth would report more positive feelings and preferences for solitude compared to younger youth, as well as spend more of their physical alone time on-line compared to younger with increased social and academic pressures becoming more digitized (Coplan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…We also investigated the links between solitary activities and adjustment outcomes such as feelings of loneliness, self-perceptions, emotional well-being, and personal happiness. Finally, based on past studies that suggest that solitary preferences and experiences may differ across adolescence (Hipson et al, 2021), and that girls and boys may have different motivations for being alone and have different thoughts and feelings while alone (McVarnock & Closson, 2022), we checked for differences in girls' and boys' responses, as well as between early and mid-late adolescence. Based on past research, we expected to find that older youth would report more positive feelings and preferences for solitude compared to younger youth, as well as spend more of their physical alone time on-line compared to younger with increased social and academic pressures becoming more digitized (Coplan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Nelson et al [27] found that U.S. emerging adults attending university with higher levels of shyness reported lower relationship quality with friends, parents, and romantic partners. Similarly, McVarnock and Closson [16] reported that shyness was positively related to test anxiety (i.e., having upset feelings during tests) and negatively associated with intrinsic values (i.e., liking what is being taught in courses) and self-efficacy (i.e., learning the materials for courses) in a sample of Canadian university student emerging adults. However, not all shy individuals are at risk for poorer adjustment.…”
Section: Motivations For Social Withdrawalmentioning
confidence: 92%
“…Sci. 2023, 13, 977 2 of 16 In this study, we focused our attention on aspects of solitude related to social withdrawal, which is defined as the tendency to remove oneself from opportunities for social interactions with familiar and unfamiliar peers [11]. Socially withdrawn individuals tend to avoid social situations and spend more time alone than their more sociable counterparts [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perilaku prokrastinasi penyelesaian studi akhir subjek juga menimbulkan oleh karena pekerjaan-pekerjaan yang membuat diri subjek lelah sehingga semua pekerjaan yang harusnya selesai menunda-nunda dalam jangka waktu yang panjang bahkan hal-hal yang sepeleh sekalipun. Subjek penelitian ini menunda-nunda menyelesaikan studi akhir dengan sejenis dalam bentuk yang berbeda misalnya bermain media social facebook tanpa batas waktu, mengikuti organisasi, malas kuliah, malas mengerjakan tugas, malas kampus, nongkorong dengan teman sampai tidak mengenal waktu, kebiasaan bermain geme online, kebiasaan nonton di media sosial facebook, tidak menajemen waktu dan tidak memiliki motivasi diri dan ketidak mampuan mengelola waktu untuk menyelesaikan studi akhir akan berdampak kepada nilai akademik (McVarnock & Closson, 2022).…”
Section: Dampak Perilaku Prokrastinasi Penyelesaiana Studi Nanti Akhirunclassified